2010
DOI: 10.1007/s10620-009-1106-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Assessing Circulating Levels of Resistin, Ghrelin, and IL-18 in Alcoholic Acute Pancreatitis

Abstract: Serum concentration of IL-18 and resistin may contribute to inflammatory response and may be useful as an early marker of inflammation in AP. We also suspect that ghrelin affects the course of AP and plays an important role in inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Serum concentrations of various inflammatory markers and mediators, for example, proinflammatory cytokines, procalcitonin, or acute phase proteins, vary between MAP and SAP patients and may help in clinical practice . The severity of AP patients shifted from mild to SAP usually after 24 h of disease admission.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of various inflammatory markers and mediators, for example, proinflammatory cytokines, procalcitonin, or acute phase proteins, vary between MAP and SAP patients and may help in clinical practice . The severity of AP patients shifted from mild to SAP usually after 24 h of disease admission.…”
Section: Discussionmentioning
confidence: 99%
“…Daniel et al evaluated the serum ghrelin levels in 32 patients with alcoholic AP and in 30 matched controls (32). The serum ghrelin concentrations on the first, third and fifth days of the study were comparable and significantly higher than in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported that ghrelin had anti-inflammatory effects both in vitro and in vivo, and was as a promising therapeutic agent in the treatment of inflammatory diseases and injury 4,27,28 . However, serum levels of ghrelin were increased in various inflammatory diseases in humans and in animal models, such as inflammatory bowel disease 29 , ankylosing spondylitis 30 , sepsis 31 , pancreatitis 32 and arthritis 33 , and increases in ghrelin levels were correlated with the disease severity and the serum levels of proinflammatory cytokines such as TNF-a and IL-6 29,31 . It was hypothesized that the elevation of serum ghrelin levels in inflammatory diseases might be a way to maintain the energy balance by controlling the body's response to systemic inflammation and stress and also to a degree, immune activation 34 .…”
Section: Discussionmentioning
confidence: 99%